2003
DOI: 10.1111/j.1744-7348.2003.tb00261.x
|View full text |Cite
|
Sign up to set email alerts
|

A new phytoplasma detected in the South Australian native perennial shrub, Allocasuarina muelleriana

Abstract: Allocasuarina muelleriana shrubs growing in natural sclerophyll roadside vegetation near Willalooka in the upper south-east of South Australia have a high incidence of a yellowing disorder in either all or part of the foliage, combined in some cases with a shortening and curling of the leaf-bearing stems. Samples from symptomatic and adjacent asymptomatic plants were tested for phytoplasmas by the polymerase chain reaction (PCR) assay. All but one asymptomatic plant were negative for phytoplasmas, whereas abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
5
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
5
2
Order By: Relevance
“…These sequence similarity values are lower than those reported previously by Gibb et al (2003), who examined only a 1152 bp 16S rDNA fragment. At the 16S-23S rDNA spacer region level, the AlloY agent differs from AP-fruit tree phytoplasmas in 11-15 % of nucleotide positions and from the SpaWB and BWB phytoplasmas in 17 and 18 % of nucleotide positions, respectively.…”
contrasting
confidence: 53%
See 4 more Smart Citations
“…These sequence similarity values are lower than those reported previously by Gibb et al (2003), who examined only a 1152 bp 16S rDNA fragment. At the 16S-23S rDNA spacer region level, the AlloY agent differs from AP-fruit tree phytoplasmas in 11-15 % of nucleotide positions and from the SpaWB and BWB phytoplasmas in 17 and 18 % of nucleotide positions, respectively.…”
contrasting
confidence: 53%
“…These findings are consistent with data obtained by putative restriction site analysis. RFLP analysis of a PCR-amplified 880 bp 16S rDNA fragment by using MseI revealed that the AlloY phytoplasma is indistinguishable from the AP and PD phytoplasmas (Gibb et al, 2003). However, when the same rDNA fragments were digested with HpaII, the AlloY phytoplasma proved to be different from both the AP and PD phytoplasmas.…”
mentioning
confidence: 99%
See 3 more Smart Citations